Pemberdayaan Komunitas Ibu Rumah Tangga Melalui Strategi Komunikasi Digital Produk Olahan Rumahan di Jagakarsa: Pelatihan Komunikasi Pelanggan dan Pengemasan Pesan Promosi - Dharta, Firdaus Yuni (Jurnal Pengabdian Kepada Masyarakat Kalam, 2024)
This community service program aims to empower housewives in Jagakarsa through digital communication strategies tailored to promote their home-based processed food products. The initiative focuses on enhancing participants' communication skills, particularly in customer engagement and crafting promotional messages that are persuasive and brand-oriented. The core activities include training sessions on effective digital communication with customers, the use of social media platforms, and techniques for packaging promotional messages that highlight product uniqueness and value. Through participatory and practical learning methods, participants are guided to build confidence in interacting with potential customers and develop communication materials that can improve product visibility and sales. The program ultimately seeks to support the economic resilience of housewives by equipping them with relevant digital skills to compete in the increasingly digital marketplace.